The Concept of Welas Asih Through Face Negotiation as Intercultural Competence - Indreswari, Esfandani Peni; Purwasito, Andrik; Satyawan, Agung (Universitas Negeri Semarang, 2020)
The act ofÃ‚Â welas asihÃ‚Â or mercy is a necessity to create peace and harmony within Indonesia's multiculturalism. This article attempts to develop the concept ofÃ‚Â welas asihÃ‚Â aiming to forgive the unforgivable which often occurred during the multicultural conflict as well as enhancing intercultural competence. The article overviews the face negotiation approaches in intercultural dialogue as a non-formal learning environment. The dialogue covers cultural conflict resolution in Indonesia, with a goal of intercultural competencies and building a better intercultural friendship. The research uses qualitative method and literature review analysis of related articles such as ethnicity conflict, face negotiation and forgiving. The result of this study shows that communicationÃ¢â‚¬â„¢s facework strategies in face negotiation are the best predictors in developing the act ofÃ‚Â welas asih. Total forgiveness after transgression is well accepted for establishing a better friendship-relationship. This discourse shows that the usage of face negotiation is essential in creating harmony, understanding cultural difference and eliminating prejudice within college studentsÃ¢â‚¬â„¢ friendships